Perceived Meritocracy and Teachers’ Willingness Toward Professional Growth in Educational Organizations - Villafuerte, Marcelo Roland; Villafuerte, Ma. Shayne Rose (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined teachers’ perceptions of meritocracy and their willingness for professional growth at Camarines Sur National High School. Anchored on the concept of meritocracy and Maslow’s theory of esteem needs, the study investigated meritocracy in terms of promotion, recognition, and incentives, and professional growth through schooling, professional learning, and acceptance of additional workloads. The research employed a quantitative descriptive-correlational design involving 436 regular permanent teachers categorized as novice and tenured teachers. A researcher-made questionnaire consisting of 36 indicators measured the variables using a 5-point Likert scale. Data were analyzed using weighted mean, average weighted mean, Analysis of Variance (ANOVA), and Spearman Rank Correlation. Findings revealed that teachers generally perceived meritocracy as moderately evident, particularly in promotion and recognition, while incentives were perceived as least evident. Teachers demonstrated willingness for professional growth through schooling and professional learning but were less willing to accept additional workloads due to workload stress, insufficient recognition, and inadequate compensation. Statistical analysis showed no significant difference between teachers’ perception of meritocracy and willingness for professional growth; however, a significant positive association existed between these variables, indicating that perceptions of fairness and merit-based practices influence teachers’ motivation and professional development. The study further proposed an alternative promotional scheme emphasizing fairness, transparency, teaching performance, and professional contributions. The study recommends strengthening transparent promotion, recognition, and incentive systems while improving workload management and professional support programs. The research aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 16 (Peace, Justice, and Strong Institutions) by promoting teacher development, fair organizational practices, and institutional transparency. The study contributes to educational, institutional, and socio-economic sustainability by supporting teacher motivation, professional competence, organizational trust, and long-term educational effectiveness.